1990
DOI: 10.1128/jb.172.1.155-163.1990
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the pAD1 hemolysin/bacteriocin determinant in Enterococcus faecalis: Tn917 insertional mutagenesis and cloning

Abstract: Thirty-seven nonhemolytic/nonbacteriocinogenic mutations in Enterococcus (Streptococcus) faecalis plasmid pADi were generated by Tn917 insertion. All were found to belong to one of two complementation classes.Each class of mutants secreted either hemolysin/bacteriocin (Hly/Bac) component A or L into the culture medium. DNA encoding Hly/Bac was cloned in Escherichia coli in which both components of the hemolysin were expressed individually and collectively. The region encoding components A and L was further def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
193
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(197 citation statements)
references
References 26 publications
3
193
0
1
Order By: Relevance
“…The CylL L and CylL S proteins are modified posttranslation by CylL M (2), and the modified CylL L and CylL S proteins are secreted via CylL B , which is the ATP-binding exporter (16). The extracellular cytolysin precursors CylL L and CylL S are converted to the active cytolysin by CylA (2,22). In an early study of the ␤-hemolysin/bacteriocin (cytolysin) determinant (22), two functional domains within the operon were identified and it was found that one region encodes the toxin precursor L component, which is now known to be encoded byCylL 1 , CylL 2 , CylM, and CylB, and the other region encodes an activator A component, which is now known to be encoded by CylA and CylI (2,8,9,17,18,39).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The CylL L and CylL S proteins are modified posttranslation by CylL M (2), and the modified CylL L and CylL S proteins are secreted via CylL B , which is the ATP-binding exporter (16). The extracellular cytolysin precursors CylL L and CylL S are converted to the active cytolysin by CylA (2,22). In an early study of the ␤-hemolysin/bacteriocin (cytolysin) determinant (22), two functional domains within the operon were identified and it was found that one region encodes the toxin precursor L component, which is now known to be encoded byCylL 1 , CylL 2 , CylM, and CylB, and the other region encodes an activator A component, which is now known to be encoded by CylA and CylI (2,8,9,17,18,39).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular cytolysin precursors CylL L and CylL S are converted to the active cytolysin by CylA (2,22). In an early study of the ␤-hemolysin/bacteriocin (cytolysin) determinant (22), two functional domains within the operon were identified and it was found that one region encodes the toxin precursor L component, which is now known to be encoded byCylL 1 , CylL 2 , CylM, and CylB, and the other region encodes an activator A component, which is now known to be encoded by CylA and CylI (2,8,9,17,18,39). In the complementation experiment between the A component-producing strain or the wild-type strain and the L component-producing strain on blood agar plates, the ␤-hemolysis zone occurred around or along the L component-producing strain (22), indicating that the A component activates the L component extracellularly and that the activated L component possesses the ␤-hemolysin/bacteriocin activity and an excess of extracellular A component is present in the culture medium of the wild-type strain (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations